B Effects: Bonds of Form and Time in Barthes, Blanchot and Beckett. Issue 2 (July 2022) - Milesi, Laurent
Abstract : Starting from Nicholas Zurbrugg's dismissal of the negative 'B-Effect' in postmodernism, which he associates with 'Benjamin, Brecht, Beckett, Barthes, Baudrillard, and Bourdieu', this essay examines the common rationale behind convergent affirmations of a neutrality or minimalism, often mistaken for nihilism, at key junctures in the works of Samuel Beckett and Roland Barthes, adding Maurice Blanchot as a critical link. The argument unfolds along a double axis: it first considers the formal role of 'chatter' or 'idle speech' and the fragment(ary in writing) in the three 'B-writers' before relating them to different constructions of temporality, such as the 'future anterior' and the après-coup, in their thematizations of 'catastrophe' and 'disaster' as indirect responses to personal or historical trauma and death. A brief concluding paragraph highlights how time's suspensiveness leads to different forms of waiting across Barthes, Blanchot and Beckett.